The Use of Blended Learning Strategy in Teaching Practicum Program: Indonesian Pre-Service Teachers' Perspectives - Devi Purmayanti; Ni Putu Amelia Artika; Edwin Nuvianto Al Aziz Aziz (Universitas Negeri Surabaya, 2025)
Internet-based technologies have greatly changed the field of education, especially in Indonesian higher education. Some schools have chosen a hybrid approach by integrating online learning, which gradually enhances the adoption of blended learning in the classroom. This study investigates how the EFL pre-service teachers in Indonesia perceive their experience as a teacher who uses a blended learning strategy in their teaching practicum program. The participants were some pre-service teachers from Islamic State Colleges in Indonesia who implemented blended learning strategy in their teaching practicum programs. The research design used in this study is a qualitative study, and the data collection method is a semi-structured interview. The data were analyzed by using thematic analysis in accordance with the TPACK as the theoretical framework by Koehler and Mishra. The findings indicated that the online learning component of blended learning facilitated both pre-service teachers’ self-efficacy improvement and their flexibility in choosing the teaching platforms, teaching time and place depending on their needs. However, the pre-service teachers faced challenges such as technical problems, limited resources, and face-to-face teaching preference. Considering the complexity of blended teaching practice, the scope of this study is very limited. Therefore, future research may need to explore how pre-service teachers' technical, pedagogical, and subject expertise interact with their teaching experiences.